Proceedings of the sixth international coral reef symposium, Townsville, Australia, 8th-12th August 1988 (Townsville, QLD. International Coral Reef Symposium, 1988)
Contents: v.1 Plenary addresses and status reviews; v.2 Contributed papers (Mini Symposium 1 to 10/14); v.3 Contributed papers (Mini Symposium 11-11/16 to 22)
Keywords: Coral reefs and island; Coral reef ecology; Coral reef conservation